The Characterization of Green Materials of Moringa oleifera Leaf Powder (MOLP) from Madura Island with Different Preparation Methods. Issue 1 (May 2019) - Susanto, Hendra; Taufiq, Ahmad; Sunaryono; Imam Mawardi, Ahmad; Hariyanto, Yuanita A; Nicholas Gerry, A; Tri Yunisa, Dinda; Rufiandita, Fahdina; Faris; Nizarghazi; Alifi, Gufron; Lita Neldya, P; et al.
Abstract: Recently, the exploration of biomaterials offers a potential property as the essential target for advanced bioengineering and its application. The local biodiversity of the Indonesian archipelago, Moringa oleifera grows and is spread quickly in the Madura island. Moringa oleifera ingredients show to be promising biodiversity for green materials development particularly in biomedical engineering. Importantly, Moringa oleifera leaf powder (MOLP) consists of some essential minerals including potassium, calcium, magnesium, sodium, iron, manganese, zinc, copper, and phosphor. However, it still lacks information about the exact minerals content within this local Moringa. This study aimed to characterize the basic minerals compound in the dried leaf or Moringa leaf powder (MOLP) from Madura Island varieties. In this study, two samples of Moringa leaf powder (MOLP) were used, and the mineral content was measured by X-ray fluorescence spectroscopy (XRF) analysis. Both samples were collected from the conventional/traditional dried method and advanced preparation. Significantly, the essential pattern of minerals concentration was found in both Moringa leaf powder (MOLP) samples. The higher level of calcium, potassium, copper, zinc, and sulfur was observed while the lower level of iron, phosphor, and magnesium was recorded by modern method. On the other hand, the different data were reported from conventional leaf powder preparation which was the higher-level minerals were dominated by calcium, potassium, zinc, copper, and iron while the lower concentration of phosphor was found. Hence, the baseline data of minerals levels provide primary information for the future development of these green materials related to the medical application and nanomaterials synthesis.